The chemical compositions and carbon structures of pine sawdust- and wheat straw-derived biochars produced in air-limitation, carbon dioxide, and nitrogen atmospheres, and their variation with charring temperature. (1st May 2022) - Yu, Shuhan; Wu, Liang; Ni, Jinzhi; Zhang, Huiying; Wei, Ran; Chen, Weifeng
Highlights: N2 and CO2 pyrolysis retained more organic carbon than air-limitation (AL) pyrolysis. AL, CO2, and N2 pyrolysis made chemical groups have different temperature trends. CO2 and N2 pyrolysis made biochar have more CC/CC groups than AL pyrolysis. AL and CO2 pyrolysis supported CO to retain in biochar relative to N2 pyrolysis. With elevated temperature, AL pyrolysis decreased the graphitic carbon content. Abstract: Currently, the effects of various pyrolysis atmosphere types (air-limitation, carbon dioxide, and nitrogen) on the chemical compositions and carbon structures of biochar remain little known. Elemental analysis, X-ray photoelectron spectroscopy (XPS), two-dimensional perturbation correlation infrared spectroscopy (2D-PCIS), and Raman spectroscopy were applied to investigate the chemical compositions and carbon structures of pine sawdust- and wheat straw-derived biochars produced in air-limitation, carbon dioxide, and nitrogen atmospheres, as well as their variation with the charring temperature. The results showed that, of the three atmospheres, air-limitation pyrolysis made biochar contain more inorganic elements, while carbon dioxide and nitrogen preferred to retain organic carbon in biochars. The 2D-PCIS spectra indicated air-limitation pyrolysis supported to retain methylene of glucopyranose ring, while carbon dioxide and nitrogen pyrolysis promoted its breaking. Carbon dioxide and nitrogen pyrolysis made an earlier decline in H-bond of alcohol and phenolic groups than methylene, and air-limitation pyrolysis presented an opposite trend. The XPS spectra showed that, at 450–750 °C, biochars produced in carbon dioxide and nitrogen had more surface CC/CC groups than biochars produced in air-limitation. Furthermore, the content of CO followed the order of nitrogen > or ≈ carbon dioxide > air-limitation at 300 °C, and was approximately equivalent at 450–750 °C for the three atmospheres. Air-limitation and carbon dioxide pyrolysis supported more CO to retain in biochars than nitrogen pyrolysis. With elevated charring temperature, the carbon content of graphitic structure decreased for biochars produced in air-limitation and increased for biochars produced in carbon dioxide and nitrogen. The carbon content of graphitic structure followed the order of air-limitation > carbon dioxide ≈ nitrogen at a relatively low charring temperature and carbon dioxide > nitrogen > air-limitation at a relatively high charring temperature. The results provide an important direction for selecting suitable pyrolysis atmospheres to optimize the properties of biochars.